Extrinsically microporous polymer membranes derived from thermally cross-linked perfluorinated aryl-ether-free polymers for gas separation - Ju Ho Shin; Hyun Jung Yu; Jiyoon Jung; Heseong An; Jung Hoon Park; Albert S. Lee; Jong Suk Lee (Nature Communications)
Abstract State-of-the-art membranes derived from polymers of intrinsic microporosity offer promising alternatives to energy-intensive, thermally driven separation techniques but often suffer from reduced performance under condensable gases or physical aging. Here, extrinsically microporous polymer membranes (EMPMs) are introduced as a distinct class of microporous membranes, fabricated from perfluorinated aryl-ether-free aromatic polymers via defluorination-induced thermal cross-linking. This process generates extrinsic micropores, increases intersegmental distances, and significantly enhances gas permeability. EMPMs exhibit a Brunauer-Emmett-Teller surface area of 552 m2 g−1 and demonstrate exceptional plasticization resistance under equimolar CO2/CH4 mixed gas at pressures up to 40 bar. CO2 permeability increases from 280 to 12,000 Barrer at 1 bar and 35 °C, while CO2/N2 selectivity reaches 46 at −20 °C, surpassing the 2019 polymeric upper bound. Furthermore, extrinsically microporous hollow fiber membranes prepared via dip-coating achieve a CO2 permeance of 2174 gas permeation units and CO2/N2 selectivity of 30 at −20 °C, highlighting their industrial relevance. This study establishes a scalable method for fabricating high-performance microporous polymeric membranes with exceptional stability for sustainable energy and environmental applications.